7 - Perceptions de la « justice des vainqueurs » : engagements de la CPI et processus de paix et de réconciliation en Ouganda, en République démocratique du Congo et en Côte d’Ivoire - Malewa, Jean-Pierre Fofé Djofia (Africa Development, 2021)
The cycle of atrocities experience in the three countries that constitute our field of study drawn primarily its source from the fight for power conquest or conservation, coupled with non-compliance with the rules. Annihilation of democratic alternation mechanisms in power in these States, defined as republic, generate armed conflict infected with crimes against humanity and war crimes perpetrated by various belligerents. During the Intermittence of lulls, claims for justice and desire for peace emerge as major concerns. How can they be responded to? What should be given priority ? Justice ? Which one ? Or peace rather ? Which peace? When we analyse, true justice: independent, impartial, fair to all; and true peace are not incompatible. The national and international mechanism to be deployed must move towards the triumph of the one for the other to come to reality and for sustainable reconciliation to reign. The ICC has all the legal assets which enable it to significantly contribute to that, provided these assets are put to work efficiently.